KEY SUCCESS FACTORS IN THE FAST FASHION BUSINESS DURING A PANDEMIC - Valerie, Margaret; Elvina, Janet; Cristie, Lizzet; Litania, Lidya; Tjoandra, Matthew; Widjojo, Handyanto (ULTIMA Management, 2022)
Abstract - Fashion offers the ability to express one's lifestyle and personality. This study aims to determine the factors that influence people's purchasing preferences for fast fashion compared with slow fashion during the COVID-19 pandemic. Mixed-method research was conducted through literature reviews, interviews, focus group discussions, and a survey. The qualitative research findings reveal that consumers prefer purchasing fast fashion compared to slow fashion. Afterward, the quantitative research was performed on 245 data sets gained from online questionnaires. The respondents involve those who bought fast fashion in the last three months. Results from regression analysis using SPSS prove that price, style, social media, and brand positively affect purchasing preferences for fast fashion. This study offers a presage for the fashion industry to build the value of the brand by considering the concoction of price and style as well as communicating it through the proper social media. Keywords: Fast Fashion; Price; Style; Social Media; Brand; Buying Preferences